O efeito reverso da idade relativa no futebol profissional: an??lise do valor de mercado e do desempenho esportivo - Ramos Filho, Luiz Antonio de Oliveira (2017)
The relative age effect on sports has already been proven in several modalities and countries, in which athletes born in the initial months of each year have a competitive advantage in physical and psychological maturation compared to those born in the final months. This phenomenon occurs due to mistakes in the decision making of coaches and managers during the selection and promotion of the most talented athletes. However, there are indications that there may be a reverse effect of relative age, where the athletes born at the end of the year reach the adult category with higher technical quality, higher sports performance and higher market value than athletes born earlier in the year. This study analyzes the existence of the reverse relative age effect, based on market value and sports performance in a sample of Brazilian professional soccer athletes from the clubs of the Brazilian Championship 2015 ??? First Division. The data were collected in the database www.transfermarkt.pt and were analyzed by parametric linear regression and non-parametric chi-square test. The results indicate that the reverse relative age effect was demonstrated in relation to sports performance, but not in relation to market value. This study has the potential to contribute to the conceptual understanding of the phenomenon and to support better decisions in a management environment perspective of coaches and managers. Focusing on the Brazilian context, as an empirical context, contributes to the line of research on these phenomena in the field of sports management in the Brazilian academy and the training of new athletes.